(untitled) (Islas, 2025)
Introduction: This article is part of the CREA-CONSTRIDIOMS research project, which explores the creativity arising from phraseological constructions in English, German, and Spanish. The current study focuses on the German proverb Morgenstund hat Gold im Mund and the Spanish proverb A quien madruga, Dios le ayuda, using a corpus-based analysis with the esTenTen23 and deTenTen23 corpora (Sketch Engine). The goal is to identify convergences and divergences in both lexical and pragmatic-discursive aspects. Specifically, the study examines the relationship between phraseology and creativity by analyzing the proverbial patterns [Morgenstund hat X im Mund] and [A quien madruga, X le ayuda]. Methods: The research method, based on phraseological studies, will be both descriptive-empirical and theoretical-analytical. It is framed within both the qualitative and quantitative paradigms, with an emphasis on the description and interpretation of data. Results: The modifications of the proverbs under study deviate depending on the context of the holistic meaning of the proverb, resulting in playful, comic, or extravagant effects. Therefore, language is shown to be creative, as evidenced by the frequency of hapax legomena—words or expressions that occur only once in the consulted corpora. Conclusions: Phraseological language is inherently productive and creative, and according to the principles of construction grammar, the high degree of fixedness in proverbs encourages their creative use. This is further reinforced by the very nature of proverbs themselves, which are conceived as constructions with a holistic meaning that can be modified.